Influence of pipe geometric deviation on bristled in-pipe mobile robot locomotion. (10th May 2018) - Galajdová, Alena; Virgala, Ivan; Kelemen, Michal; Miková, Lubica; Lipták, Tomás; Kelemenová, Tatiana
This article deals with the analysis of geometric deviations influence on in-pipe robot locomotion, which uses the principle of friction difference principle. Bristles are as carrying elements. They are mounted as cantilever beams at angle to robot body. The robot should locomote inside industrial pipelines. All pipes have geometric deviations, which come from production process otherwise from operation process. It is necessary to know about the influence of these geometric deviations on the robot locomotion.